2004
DOI: 10.2105/ajph.94.12.2098
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Disparities and Cervical Cancer

Abstract: Our study underscores the importance of cervical cancer screening programs targeted at low-income women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 23 publications
4
33
0
9
Order By: Relevance
“…In articles that examined cervical cancer survival and SES, 6,7,14,16-23 6 of 11 studies indicated that women with lower SES had poorer survival. 6,7,17,[20][21][22] Eggleston et al 7 reported on 5467 women with cervical cancer. In their study, an SES variable was defined by using measures of employment, income, education, and poverty at the zip code level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In articles that examined cervical cancer survival and SES, 6,7,14,16-23 6 of 11 studies indicated that women with lower SES had poorer survival. 6,7,17,[20][21][22] Eggleston et al 7 reported on 5467 women with cervical cancer. In their study, an SES variable was defined by using measures of employment, income, education, and poverty at the zip code level.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,14,[16][17][18][19][20][21][22][23] Unlike information on stage and treatment, however, databases used by public health researchers generally do not include information on individual SES. SES has been described in the cervical cancer literature using various combinations of measures, including poverty level, occupation, educational level, and insurance status.…”
mentioning
confidence: 99%
“…Algunos de estos son la morbilidad 1,2,3,4,5,6 , la mortalidad 7,8,9 , así como con la prestación de servicios de salud en la población 1,10,11,12 . La dirección general que sigue esta relación es que a medida que desciende la posición socioeconómica, los indicadores de salud son peores.…”
Section: Introductionunclassified
“…Las desigualdades en el diagnóstico y supervivencia de cáncer en relación a determinantes sociales están bien documentadas 9,15 . Los programas para reducir las desigualdades se han convertido en objetivos prioritarios en nuestro entorno y así lo pone de manifiesto la Estrategia Nacional de Equidad en Salud.…”
unclassified